2015
DOI: 10.1016/j.chemgeo.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic isotopes for deciphering terrigenous input provenance in the western Mediterranean

Abstract: Radiogenic isotopic signatures in marine sediments can be used to trace terrigenous source areas and transport mechanisms, which are in turn related to climate variability. To date, most of the published studies using this approach have been focused on eastern Mediterranean sediments. In contrast, we study here the terrigenous input provenance in the westernmost Mediterranean

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 121 publications
1
20
0
Order By: Relevance
“…Montagna, personal communication, 2016). This is in agreement with εNd results obtained by Jiménez-Espejo et al (2015) from planktonic foraminifera collected from deepwater sites (1989 and 2382 m) in the Alboran Sea (Fig. 4c).…”
Section: Hydrological Changes In the Alboran And Balearic Seas Since supporting
confidence: 82%
See 1 more Smart Citation
“…Montagna, personal communication, 2016). This is in agreement with εNd results obtained by Jiménez-Espejo et al (2015) from planktonic foraminifera collected from deepwater sites (1989 and 2382 m) in the Alboran Sea (Fig. 4c).…”
Section: Hydrological Changes In the Alboran And Balearic Seas Since supporting
confidence: 82%
“…The Early Holocene is characterized by a collapse of the LIW (Kuhnt et al, 2008;Schmiedl et al, 2010;Toucanne et al, 2012) synchronous with the sapropel S1 deposition (10.2-6.4 cal ka BP; Mercone et al, 2000). Proxies for deep-water conditions reveal the occurrence of episodes of deep-water overturning reinforcement in the eastern Mediterranean basin at 8.2 ka BP (Rohling et al, 1997(Rohling et al, , 2015Kuhnt et al, 2007;Abu-Zied et al, 20082015), responsible for the interruption of the sapropel S1 in the eastern Mediterranean basin (Mercone et al, 2001;Rohling et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these low LOI values hydrothermal alteration is likely to have mobilised some of the major elements and the large ion lithophile (LIL) elements (Ba, Rb, Sr, and K), as has been documented in numerous studies (e.g., Pearce, 1996;Polat and Hofmann, 2003). However, the high field-strength (HFS) elements such as Nb, Ta, Zr, Hf, Y and Th are generally regarded to be relatively immobile during low-temperature alteration (e.g., Pearce and Cann, 1973;Polat et al, 2002 Sr seawater (e.g., Kawahata et al, 2001;Godard et al, 2006), Nd and Pb radiogenic isotope ratios are relatively insensitive to alteration and are much more reliable indicators of magmatic sources (Rodrigo-Gámiz et al, 2015;Simon et al, 2017). We therefore use immobile trace elements along with Nd and Pb radiogenic isotope ratios as well as field observations and regional constraints in our assessment of the petrogenesis and tectonic setting of these rocks.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent lack of coherence in the U1386B/C signal between Sr isotope ratios and the composition of detrital continental or eolian components (Figs. 3C, 9B, C), with climate stages, must be explored further as a matter of process versus source (as in the Alboran Sea by Rodrigo-Gámiz et al, 2015). The glacial-MOW interglacial-AW model is nevertheless in agreement with what occurred over the last glacial-Holocene cycle (Lebreiro et al, submitted for publication).…”
Section: Past Variability Of the Early-pleistocene Mow Fossil Moat Inmentioning
confidence: 86%
“…Their findings do not indicate contrast between the last glacial-Holocene cycle. In the Alboran Sea, however, Rodrigo-Gámiz et al (2015) have reported a Pb shift in terrigenous eolian source from northern Africa and South Iberia and France during the LGM to more European during the Holocene.…”
Section: Introductionmentioning
confidence: 93%